Analiza in ovrednotenje rezultatov medlaboratorijskih primerjav na področju meritev temperature v okviru Svetovne meteorološke organizacije (WMO) - Begeš, Gaber (Elektrotehniški vestnik, 2025)
This paper presents the ongoing global interlaboratory comparison (ILC) for temperature measurement organized by the World Meteorological Organization (WMO), planned and coordinated by LMK. The ILC follows a protocol developed under the METEOMET project, which promotes cooperation between meteorological and metrological laboratories. Only temperature results are discussed, although the ILC also covers humidity and pressure. The analysis uses the En number to assess the participating laboratories’ proficiency. Most laboratories demonstrated acceptable results (|En| ? 1), but deviations in RA I and RA III suggest methodological or technical issues. The ILC has proven to be a valuable tool for assessing measurement competence and identifying improvement opportunities in laboratory practices
Keywords: data model; data spaces; digital twin; digitalni dvojček; NGSI-LD; podatkovni model; podatkovni prostori; RDF; semantic interoperability; semantična interoperabilnost